Microbial Contamination of Water in Around Dhaka City - Parveen, Sahana; Ahmed, M Shakir Uddin; Nasreen, Tania (Bangladesh Journal of Scientific and Industrial Research, 2008)
A total of 109 water samples were collected from around Dhaka city and examined for microbial contamination. Samples were collected in sterilized screw capped glass bottles, transported to the laboratory in cold and processed within 6 hours of their collection. All river water, pond water and household water were found heavily contaminated with coliform, faecal coliform, E. Coli and Salmonella whereas tube well water and bottled water was devoid of faecal coliform, E. Coli and Salmonella. A significant correlation between total number of total coliform and percentage of Salmonella was also investigated. It is suggested that water must be boiled before use. Key Words: Water contamination, Total coliform, Faecal coliform, Salmonella DOI: 10.3329/bjsir.v43i2.972 Bangladesh J. Sci. Ind. Res. 43(2), 273-276, 2008